A climatology of lee waves over the UK derived from model forecasts. (30th March 2012) - Vosper, S. B.; Wells, H.; Sinclair, J. A.; Sheridan, P. F.
ABSTRACT A lee wave forecast system has been run operationally at the UK Met Office since 2006. The forecasts are produced by a numerical model for flow over complex terrain (3DVOM) which is run for five separate hilly regions across the UK. These regions cover Dartmoor (southwest England), Snowdonia (north Wales), Cumbria and the Pennines (northern England), the Grampians (Scotland) and the Mourne and Sperrin mountains (Northern Ireland). Examples of verification of the model forecasts against aircraft and satellite observations are presented. Three years of forecast data for these regions have been used to generate a lee wave climatology for the UK. The model predicts large geographical differences, with lee waves occurring least frequently over Dartmoor and most frequently over Snowdonia and the Grampians. Large amplitude waves, with peak vertical velocities exceeding 3 m s−1 at 700 hPa or above, are more common in forecasts for the Grampian region than others. Lee waves occur more frequently in forecasts during winter months than in summer. The most favourable conditions are those in which there is little turning of the lower tropospheric winds and analysis suggests that the waves are typically trapped in the lower troposphere. The influence of the lee waves on the near‐surface flow has also been investigated. Large accelerations and flow deflections can occur beneath the waves. It is suggested that the latter correspond to turbulent lee wave rotors. Preferred locations for this behaviour have been identified in the model forecasts for the Grampians and Pennines.